Kaffir lime leaf - S. Wongpornchai (2018)
© Woodhead Publishing Limited, 2012. The kaffir lime leaf, or Citrus hystrix, is part of the Rutaceae family. It is known by various different names, the etymology of which is discussed in this chapter. The areas and systems of cultivation, diseases and pest control, production technology and marketing of kaffir lime leaves are also introduced in this chapter. Research methods for the analysis of the chemical composition of essential oils or extracts from the kaffir lime leaf are reviewed and discussed together with their biological activities. Finally, the uses of fresh leaves and their essential oils in the food and cosmetics industries are considered.